Preliminary Study: Construction of the Indonesian Family Function Measuring Instruments - Yun Nina Ekawati; Nofrans Eka Saputra (Journal of Educational, Health and Community Psychology, 2021)
This study aimed to construct a scale to measure the family functioning of high school students by using the principal component analysis (PCA) technique. The population of this research was high school students in Jambi Province. The number of sample used was 319 respondents by a random sampling technique. The result of the analysis showed that the constracted validity by using the principal component analysis method with orthogonal rotation and varimax extraction result in eight components that were succesfully extracted into affection factor, educational socialization, environmental development, economy, religion, reproduction, socio-cultural, future protection. Each component had correlation coefficient 0,000 which means each component measures different aspect. It was independent and it did not have correlation toward each other.The reliability test by using the Guttman Method generated valueÂ Î»=0.983 which means that this scale had a good degree of confidence to measure family function of high school students and it can be used.Â